2017
DOI: 10.1080/03630242.2017.1306604
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with general and health-related quality of life in menopausal transition among women from Serbia

Abstract: This study assessed factors associated with quality of life (QOL) among Serbian peri- and postmenopausal women using two menopause-specific scales. This cross-sectional study included 500 women aged 40-65 years who had a gynecologic check-up in one of two Community Health Centers in Belgrade during February 2014 to January 2015. Women completed: a questionnaire about socio-demographics, habits, and health status; a menopause-specific questionnaire, Utian's Quality of Life Scale (UQOL); and a Women's Health Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
5
12
0
Order By: Relevance
“…HRQoL has been shown to decrease with age [26,27], and Kvamme et al [28] reported that, within the BMI categories, moderately overweight individuals had the highest HRQoL. Furthermore, the finding that higher educational and income levels were associated with a high HRQoL is consistent with that of a previous study in middleaged and elderly adults showing that individuals in the higher education and income groups had a higher HRQoL than those in the lower education and income groups [29][30][31][32].…”
Section: Discussionsupporting
confidence: 73%
“…HRQoL has been shown to decrease with age [26,27], and Kvamme et al [28] reported that, within the BMI categories, moderately overweight individuals had the highest HRQoL. Furthermore, the finding that higher educational and income levels were associated with a high HRQoL is consistent with that of a previous study in middleaged and elderly adults showing that individuals in the higher education and income groups had a higher HRQoL than those in the lower education and income groups [29][30][31][32].…”
Section: Discussionsupporting
confidence: 73%
“…11 Previous studies showed that working women might have better QoL in the menopausal and postmenopausal stages than those unemployed or housewives, as they might have better access to health care, better economic stability, social interaction and empowerment which all might reduce the physical symptoms of menopause. 8,[11][12][13][14][15][16][17] One study measured Serbian women's QoL using the Utian menopausal QoL scale, which has one specific domain measuring the occupational QoL and found that that employment and economic status were correlated with the occupational domain in QoL. 14 Jordanian women at menopausal age Bustami et al, 18 conducted a cross-sectional study to assess factors associated with onset of premature/early menopause among 409 Jordanian women.…”
Section: Introductionmentioning
confidence: 99%
“…Greater palpitations were associated with poorer menopausal QOL, 47 poorer physical (but not mental) component QOL, 53 poorer sleep-related QOL, 56 and poorer occupational QOL. 56 In contrast, palpitations were not related to general 51 or sexual 61 QOL.…”
Section: Resultsmentioning
confidence: 93%
“…The association between palpitations and QOL was similar across different QOL constructs and measures (e.g. menopause QOL, 47 physical component QOL, 53 sleep-related QOL, 56 and occupational QOL), 56 yet there was only one study for each of these measures. Review findings suggest palpitations may be important to women’s QOL; however, additional research to confirm the association is needed.…”
Section: Discussionmentioning
confidence: 94%